Design and Implementation of P&O Maximum Power Point Tracker Algorithm Based Solar Charge Controller - Hakan Yahya AKDENIZ; Ahmet YÖNETKEN (International Journal of Applied Methods in Electronics and Computers, 2019)
: Solar energy is one of the main sources of renewable energy. In photovoltaic systems, energy is obtained from photovoltaic batteries In photovoltaic batteries, the current and voltage do not increase linearly. This causes the power to take different values. There is a point where power reaches its peak. Detecting this point called the maximum power point and transferring the energy to the load at this point, reduces the losses and increases the efficiency. Many microcontroller controlled circuits have been designed and algorithms have been developed for maximum power point trackingPerturb and Observe algorithm is the most widely used algorithm. In this study; Maximum Power Point Tracker Algorithm Based Solar Charge Controller is designed. Arduino microcontroller card was used as it has easy programmability and rapid prototype development. Developed charge regulator determines the maximum power point by measuring the current voltage values and charge the battery at this point. The current, voltage, battery charge rate and charge status information obtained from the charge controller can be monitored by android mobile devices. The developed charge control circuit has been tested using a 45 Watt photovoltaic panel under different weather conditions. It was observed that it followed the maximum power point.